The Lorenzo Diaries: phraseological and paremiological characterisation of the protagonist - de la Fuente, Barbadillo Teresa M.ª (Romanica Olomucensia, 2024)
Three novels published by Miguel Delibes over a period of forty years - between 1955 and 1995 - have as their protagonist Lorenzo, a hunter, emigrant, and pensioner, respectively, who through the procedure of an assumed speaker reflects his experiences, thoughts, and reactions in diaries of varying length and location. Lorenzo is a less sombre character than others in the narrative gallery of the writer from Valladolid, who showed particular sympathy for him, mainly because of the hunting hobby they shared, even though he was aware that in the course of those years the character changed, in spite of his own creator. The aim of this paper was to study Lorenzo's speech and, from there, to make a judgement on it. The methodology used was the collection of the phraseological and paremiological samples that Miguel Delibes put in the mouth of this character and, subsequently, their analysis. The result is that Lorenzo's speech contains numerous and varied phraseological units, representative of colloquial practice - some of them of vulgar register - as well as units from the proverbial wealth of the Spanish language of the 20th century. This work collects, classifies, and makes observations on representative samples of both kinds of unit from the three diaries. In this way, evidence of Delibes' artistic rendering of the expressive use of the Spanish language is offered, as a consequence of which the reader has the impression that he is listening to the protagonist's own account.
Keywords: phraseology; paremiology; Miguel Delibes; Lorenzo's Diaries